2009
DOI: 10.1007/978-1-4419-5692-7_50
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase to Double Breathing Rate Appears During REM Sleep in Synchrony with REM –A Higher CNS Control of Breathing? –

Abstract: Breathing rate (BR) during rapid eye movement (REM) sleep is known to fluctuate largely, while increases in BR during REM sleep reported were small. In our mice experiments, we found that mice exhibit a rapid increase in instantaneous BR (RIBR) of >2 fold during natural sleep with accompanying atonia, laying their sides down. The RIBR was further found in a sleeping mouse attached with EEG electrodes when the EEG amplitude and delta wave power were lower. Therefore, it is likely that mice show RIBRs during REM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…After a literature search we found one published case report describing REM sleep-related tachypnea to the degree seen in our studies, double the baseline breathing rate. 5 However, the previous case report was observed in normal healthy volunteers and tachypnea was thought to be mediated due to direct spinal reflex pathways, to the best of our knowledge this direct spinal reflex pathway in humans has not been described anywhere else in literature yet. In our case series, chart review and data corroboration showed that events occurred during PAP titration studies with high PAP pressures (pressure ranges IPAP 18-25 cmH 2 O and EPAP 14-17 cmH 2 O).…”
Section: Discussionmentioning
confidence: 77%
“…After a literature search we found one published case report describing REM sleep-related tachypnea to the degree seen in our studies, double the baseline breathing rate. 5 However, the previous case report was observed in normal healthy volunteers and tachypnea was thought to be mediated due to direct spinal reflex pathways, to the best of our knowledge this direct spinal reflex pathway in humans has not been described anywhere else in literature yet. In our case series, chart review and data corroboration showed that events occurred during PAP titration studies with high PAP pressures (pressure ranges IPAP 18-25 cmH 2 O and EPAP 14-17 cmH 2 O).…”
Section: Discussionmentioning
confidence: 77%
“…Several researchers demonstrated that the PZT system can also detect signals from the chest and abdominal movements related to respiration (Flores et al, 2007; Sato et al, 2006; Zehendner et al, 2013) in addition to heartbeat sounds. These signals may also be included into the sleep scoring to improve REM sleep detection because significant fluctuations of these parameters are known to occur in REM sleep (Sato et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…11,12 The decreased breathing rate during NREM sleep elevates pCO 2 and reduces blood pH, 10,13−16 but the levels become normal with the increased breathing rate during REM sleep. 17 Hence, possibly, one of the functions of REM sleep could be to maintain the normal pH and the homeostatic balance of pCO 2 during sleep. 10 The locus coeruleus (LC) neurons are intrinsically chemosensitive, and they respond to a drop in the extracellular pH by increasing their firing rate and concomitantly elevating the breathing frequency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although REM sleep is crucial for survival, it is not present in all organisms, rather found only in terrestrial birds and mammals. ,, Further, many studies suggest that breathing and heart rates decrease during a long spell of NREM sleep . On the other hand, these parameters increase during REM sleep. , The decreased breathing rate during NREM sleep elevates pCO 2 and reduces blood pH, , but the levels become normal with the increased breathing rate during REM sleep . Hence, possibly, one of the functions of REM sleep could be to maintain the normal pH and the homeostatic balance of pCO 2 during sleep …”
Section: Introductionmentioning
confidence: 99%